The morphology, development, and evolution of the head of fishes: Foundational studies for a renaissance of comparative morphology. (17th June 2019) - Hilton, Eric J.; Warth, Peter; Konstantinidis, Peter
Abstract: Acta Zoologica has played a key role as a publishing outlet for advancing zoological knowledge since its foundation in 1920 by Nils Holmgren. With the journal celebrating its centennial, we have assembled a virtual issue that celebrates some of the morphological highlights from the history of Acta Zoologica, which has been a venue for precise and detailed anatomical descriptions of the morphology and ontogeny of major vertebrate taxa. Because our own focus of research has been the evolution of the musculoskeletal system of fishes, a bias toward these topics in our selection is readily apparent. However, these papers also reflect the tradition established by Holmgren's "Studies on the Heads of Fishes, " published in Acta Zoologica . We hope that by bringing together Holmgren's "Studies, " along with a selection of other papers from across the history of the journal will inspire the continued growth of comparative vertebrate anatomy, especially in an era where advanced technologies are available. We discuss various author's approaches to morphology, including Holmgren (1877–1954), Torsten Pehrson (1887–1970), and Alexej Nikolajevich Sewertzoff (1866–1936). The foundation that was laid by these and other workers offers the basis for continued investigation and testing of hypotheses. We feel that the true testament to the power of comparative anatomy is that even after so much study and the volume of baseline data available, new and important findings continue to be made from the careful observation of anatomical form. Abstract : virtual issue